EVALUATION OF AQUEOUS AND ETHANOLIC EXTRACTS OF SYZYGIUM CARYOPHYLLATUM FOR ANTIBACTERIAL ACTIVITIES - Pendru, Raghunath; Nadipelly, Jagan; Kothapalli, Jyothinath; Kotigadde, Subbannayya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: It has been well documented that traditional medicinal plants confer considerable antimicrobial activity against various microorganisms. Methods: The present study was designed to evaluate the antimicrobial properties of aqueous and ethanolic extracts of the leaves of Syzygium caryophyllatum against Staphylococcus aureus, Escherichia coli, Salmonella typhi, Shigella flexneri, and Vibrio cholerae. The aqueous extract was prepared using cold percolation method, and ethanolic extract was prepared in Soxhlet apparatus using ethyl alcohol. Antimicrobial activity is being determined by time-kill assay and minimum inhibitory concentration. Results: From our study, it is found that all tested organisms were sensitive to both aqueous and ethanolic extract of leaves of S. caryophyllatum. The ethanolic extract showed better antibacterial activity against S. aureus and S. typhi when compare to aqueous extract. The phytochemical analysis confirmed the presence of flavonoids, alkaloids, glycosides, steroids, phenols, tannins, and saponins in the ethanolic and aqueous extract of S. caryophyllatum. Conclusion: We hypothesize that these active phytoconstitutents might be responsible for the antimicrobial activity of this plant.